2012
DOI: 10.3109/15622975.2012.690535
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for attention-deficit/hyperactivity disorder (ADHD). A consensus report of the WFSBP task force on biological markers and the World Federation of ADHD

Abstract: Most likely, no single ADHD biomarker can be identified. However, the use of a combination of markers may help to reduce heterogeneity and to identify homogeneous subtypes of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 213 publications
5
80
1
3
Order By: Relevance
“…9 Behavior rating scales, which comprise checklists that examine various behaviors and symptoms, are the most common ADHD assessment tools in schools and communities because of their uncomplicated administration and high time-and cost-efficiency. 10 The Child Behavior Checklist (CBCL) 11 and Conners Rating Scale-Revised (CRS-R) 12 are commonly used diagnostic tools for identifying ADHD in children and adolescents because of their adequately established reliability and validity.…”
mentioning
confidence: 99%
“…9 Behavior rating scales, which comprise checklists that examine various behaviors and symptoms, are the most common ADHD assessment tools in schools and communities because of their uncomplicated administration and high time-and cost-efficiency. 10 The Child Behavior Checklist (CBCL) 11 and Conners Rating Scale-Revised (CRS-R) 12 are commonly used diagnostic tools for identifying ADHD in children and adolescents because of their adequately established reliability and validity.…”
mentioning
confidence: 99%
“…The results of this study suggest a role for glutamate in ADHD. In an investigation of the association between metabotropic glutamate receptor subtype 7-gene polymorphism and treatment response to methylphenidate, children with the G/A genotype had a more pronounced response rate than children with the G/G genotype [1].…”
Section: Role Of Copy Number Variants In Adhdmentioning
confidence: 99%
“…olfactory sensitivity, substantial echogenicity) exist. The development of ADHD markers is hindered by sample heterogeneity due to etiological and phenotypic complexity and age-dependent co-morbidities [1].…”
Section: Biological Markers In Diagnosis Of Adhd Biologically Based Nmentioning
confidence: 99%
“…Some studies suggest that diet, exercise and stress may also have shortterm effects on plasma catecholamine levels in children and adolescents with ADHD 14,15 . Upon evaluating the results, some have proposed that the dopamine transporter genotype (DAT1) or methylphenidate response may be used as biomarkers, while others have underlined the importance of sample heterogeneity in studies [9][10][11][12][13][14][15] . A recent meta-analysis reported that 33.8% of the 210 studies evaluated had focused on the main metabolites and enzymes of the monoamine pathway and that norepinephrine (NE), 3-methox, 4,hydroxyphenylethylene glycol (MHPG), and monoamine oxidase (MAO) were found to be significantly different between cases and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of c o n v e r g i n g e v i d e n c e f r o m g e n e t i c s , neurophysiology, neuropsychology, neuroscience, and neuropharmacology support the role of these neurotransmitter systems in ADHD, although their interactions with other neurotransmitter systems, gender, and environmental risk factors are still not fully clarified [6][7][8] . Despite extensive evaluations of cerebrospinal fluid (CSF), blood, and urine samples from patients of variable age groups, the search for reliable and replicable biomarkers of ADHD has proven unsatisfactory [9][10][11][12][13][14][15] . Some studies suggest that diet, exercise and stress may also have shortterm effects on plasma catecholamine levels in children and adolescents with ADHD 14,15 .…”
Section: Introductionmentioning
confidence: 99%